Bullying at Work and Job Satisfaction: The Role of Perceived Organizational Support - Skuzińska, Anna (Przegląd Psychologiczny, 2025)
Aim: Job satisfaction is an important indicator of employee well-being and organizational behaviour. Intense negative work relationships (i.e. bullying) can reduce job satisfaction. Perceived organizational support (POS) is one factor that could modify this relationship (Kurtessis et al., 2017), but its role in the relationship between bullying at work and job satisfaction remains unclear (Francis, 2014). Therefore, this study aims to verify the hypothesis that perceived organizational support moderates the relationship between bullying and job satisfaction. Method: N = 203 administrative employees participated in an anonymous cross-sectional questionnaire survey. The Negative Acts Questionnaire (NAQ), the Perceived Organizational Support Scale (POS), the Job Satisfaction Scale (JSS) and the Job Affect Scale (JAS) were used. To verify the hypothesis, a hierarchical regression analysis was conducted using SPSS 29.0 software. Results: A significant interaction effect between negative acts and perceived organizational support was found to be related to job satisfaction and negative affect. However, the protective role of support was revealed only in cases of low intensity of negative acts. The job satisfaction in the group of unsupported employees declined faster than in the group of supported employees; for the latter group, job satisfaction was not significantly related to the negative acts experienced. Exposure to negative behaviors increased negative affect in both low and high POS employees. An inverse buffer effect of support emerged among employees who perceived high organizational support and experienced intense work-related acts. No interaction was found for positive affect. Conclusion: Based on the collected data, it can be cautiously concluded that perceived organizational support offers employees limited protection against reduced job satisfaction when they experience intense negative acts at work, and that it may exacerbate tension and negative emotions in some cases. Studies investigating the moderating role of POS in the relationship between bullying at work and job satisfaction should consider both the three components of job satisfaction and the various types of negative behaviors (directed at work or the employee’s personal sphere) due to the different relationship between these variables.